(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
The identity of Bosniaks is a frequent target of discriminatory treatment by the media in Bosnia and Herzegovina and its neighboring countries. Of particular concern is the fact that Bosniaks are often discriminated against through public media, that is, the media owned by the state and entity structures. Considering that there is a noticeable presence of unprofessional, unfair, and discriminatory attitude of the media in Bosnia and Herzegovina toward Bosniak identity, research was carried out with the aim of examining the media treatment of the Bosniak identity in such media. For the purposes of this work, the research was conducted on a sample of 241 respondents in the territory of the Federation of Bosnia and Herzegovina, that is, Zenica-Doboj and Sarajevo cantons. The research was carried out using a survey. After the survey, a quantitative statistical analysis of the results was done. The text includes parts of the MA thesis by Melika Hakanović; Media Treatment of Bosniak Identity in the Media within Bosnia and Herzegovina, defended at the Faculty of Political Sciences, Department of Communications in 2023.